Archeological research in 2023 in the Kogaly valley of Southeast Kazakhstan - Baigunakov, Dosbol (Journal of Posthumanism, 2025)
This article examines archeological excavations carried out in 2023 by a team from Al-Farabi Kazakh National University in the Kogaly Valley of southeast Kazakhstan. The relief of the Kogaly valley is favorable to kurgan complexes. Local ancient residents adhered to a system of “vertical” nomadism: they moved into the highlands in the spring, and returned to the lowlands in the fall. Among these picturesque valleys, they conducted burials, which continue to fascinate researchers. The Kogaly (or Kugaly) valley is known for its concentration of royal kurgans dating to the early Iron Age. Unfortunately, the large royal kurgans in the central part of the valley were extensively looted, destroying these monuments as a historical and archeological source. As a result, specialists bypassed the region for a long time. Kurgans of commoners can also be found in the valley. Such kurgans are smaller in size, although they are frequent sources of individual finds valuable to the researcher. Two kurgans dating to the early Iron Age were excavated near the village of Bostan in 2023. The external appearance of these kurgans and the design of objects and materials found within allows us to date them to the early Iron Age and determine their identity as funeral complexes for commoners.